The Development of Teak Leaf Cookies for BUMDes Gajah Mada, Pokdarwis, and PKK in Kebontunggul Village, Mojokerto - Sutanto, Tiffany Arista; Puspitasari, Elia Devina; Go, Tjie Kok; Darmasetiawan, Noviaty Kresna; Mustikasari, Hany; Widyastuti, Endang Widoeri; Angeline, Anastasia Pingkan; Anggoro, Arco (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
Kebontunggul village (Gondang district, Mojokerto, East Java, Indonesia) is abundant in teak (Tectona grandis L.) leaves, but their utilization is still lacking. Based on this potential, supported financially by Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi (The Ministry of Education, Culture, Research, and Technology/Kemendikbudristek) University of Surabaya (UBAYA) and Widya Mandala Surabaya Catholic University (WMSCU) collaborated with Badan Usaha Milik Desa (Village-owned Enterprise/BUMDes) Gajah Mada, Kelompok Sadar Wisata (Tourism Awareness Group/Pokdarwis), and Organisasi Pemberdayaan Kesejahteraan Keluarga (Family Welfare and Empowerment Organization/PKK) Kebontunggul village in Pemberdayaan Desa Binaan (Community Engagement Program/PDB). The program aims to produce cookies from teak leaves to increase the economic activity of the Kebontunggul residents. The methods used are community education, consultation, training, science and technology transfer. The focus of this specific program was before-after knowledge assessment, skill development, and community participation in teak leaf-based cookies innovation. There was an increase in the knowledge and skills of the Kebontunggul people, as indicated in the pre-test and post-test results. The training output was the procedure and formulation development of teak leaf powder and teak leaf cookies to support its production scale and increase the residents' economic activity.